THE EFFECT OF ENDORPHIN MASSAGE ON ANXIETY LEVELS IN PREGNANT WOMEN IN TRIMESTER III - Rahantan, Andria Permata; Alfitri, Rosyidah; Purwati, Anik (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2025)
Anxiety in third-trimester pregnant women is a common psychological issue that occurs as labor approaches. Unmanaged anxiety can negatively impact the labor process and the health of both mother and fetus. One non-pharmacological method that can be used to reduce anxiety is endorphin massage, a massage technique that stimulates the release of endorphins, creating a sense of calm and comfort. This study used a pre-experimental design with a one-group pre-test and post-test approach. The sample consisted of 40 third-trimester pregnant women selected using total sampling. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after the endorphin massage intervention. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed a p-value of 0.000 (α < 0.05), indicating a significant effect of endorphin massage on reducing anxiety levels in third-trimester pregnant women. It is recommended that future studies combine endorphin massage with other interventions such as aromatherapy, relaxation music, or hypnobirthing.